PENGARUH SERVICE QUALITY, PRICE, DAN PERCEIVED EASE OF USE TERHADAP CUSTOMER SATISFACTION PENGGUNA TRANSPORTASI ONLINE MAXIM - Fauzi Bagas Saputra (2023)
Maxim has become a popular online transportation in Indonesia. The industry provides effectiveness and efficiency through easily accessible services. In addressing societal challenges to meet the needs and mobility of the people, an online transportations service that aligns with user expectations is necessary. This research aims to identify, analyse, and prove the partial influence of service quality, price, and perceived ease of use on customer satisfaction among Maxim's online transportation users. The research sample consists of 100 respondents who are Maxim's online transportation users residing in East Jakarta. This is a quantitative research using primary data. The sample collection techniques uses a non-probability sampling, specifically purposive sampling method. The data used are collected through google forms, and data analysis involves both descriptive and inferential analyses. The data analysis is carried out using the SmartPLS 4.0 software. The results indicate that (1) service quality significantly influences customer satisfaction of 0.462, (2) price significantly influences customer satisfaction of 0.264, and (3) perceived ease of use significantly influences customer satisfaction of 0.246. The R-Square values obtained for service quality, price, and perceived ease of use variables contribute 67.9% to customer satisfaction, while the remaining 32.1% is influenced by other variables not included in this research.